The Advice Given During Near-Peer Interactions Before and After Curriculum Change. Issue 4 (8th August 2022) - Huang, Kelly; Mak, David; Hafferty, Frederic W.; Eva, Kevin W.
Abstract: Phenomenon Near-peer interactions (NPIs) provide formal and informal mentorship that can allow medical students to share strategies for successful training. Such capacity to convey valuable advice, however, may depend on the similitude of experiences. Given that many factors can disrupt homogeneity, including curriculum renewal, we must better understand whether junior trainees feel disadvantaged when they do not have more senior peers with similar experiences. This study was, therefore, conducted to examine the focus of, and engagement with, advice available through NPIs during curriculum renewal. Approach: We used a generic exploratory qualitative research approach. Twenty MD undergraduate students, seven from the Class of 2019 (the first cohort post-curriculum change), and thirteen from the Class of 2020 (the first cohort with access to more senior students in the new curriculum), participated in semi-structured interviews. Anonymized transcriptions were analyzed with open, axial, and selective coding to generate themes until saturation was attained. Findings: Participants from the Class of 2019 reported having particularly few reasons to seek advice; because curriculum renewal disrupted their near peers' capacity to provide critical insights, students exerted little effort to learn from them. That said, this vacuum was not generally cause for concern. Deeper probing illustrated why: advice given during NPIs in both classes more commonly focused on nonacademic (e.g., work-life balance issues) than academic advice; academic advice, when sought or offered, tended not to be aimed at improving understanding of curriculum dependent content; and, while students in both classes welcomed advice, both were wary of accepting it at face value, precluding a sense of dependence on senior peers. Insights: Students' skepticism about the overall utility of academic advice raises a number of important issues for medical education and training. Positively, it shielded students from feeling loss when advice from similarly trained students was not available, reducing concerns about disadvantage that could arise during periods of curriculum revision. On the other hand, knowing that what students perceive and what educators claim to be important aspects of training can be at odds and knowing that self-assessment is flawed makes it surprising and unsettling, respectively, that participants so readily treated the lessons learned by those who came before them as irrelevant.